R&D collaboration networks in the European Framework Programmes: data processing, network construction and selected results. (19th March 2008) - Roediger-Schluga, Thomas; Barber, Michael J.
We describe the construction of a large and novel dataset on R&D collaboration networks in the first five EU Framework Programmes (FPs), examine key features and provide economic interpretations for our findings. The dataset is based on publicly available raw data that presents numerous challenges. We critically examine the different problems and detail how we have dealt with them. We describe how we construct networks from the processed data. The resulting networks display properties typical for large complex networks, including scale-free degree distributions and the small-world property. The former indicates the presence of network hubs, which we identify. Theoretical work shows the latter to be beneficial for knowledge creation and diffusion. Structural features are remarkably similar across FPs, indicating similar network formation mechanisms despite changes in governance rules. Several findings point towards the existence of a stable core of interlinked actors since the early FPs with integration increasing over time. This core consists mainly of universities and research organisations. The paper concludes with an agenda for future research.